2021
DOI: 10.2147/ccide.s306110
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Oral Health Literacy and Number of Remaining Teeth Among the Thai Elderly: A Cross-Sectional Study

Abstract: Purpose Limited oral health literacy is associated with poor oral health status. This study aimed to determine the association between oral health literacy (OHL) and the number of remaining teeth (NRT) among Thailand’s older population. Patients and Methods This cross-sectional study was conducted between July 1, 2020 and September 30, 2020 at the Subdistrict Health Promoting Hospitals in Panare, Pattani, Thailand. A total of 361 independent-living older adults, male an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Recent studies indicated that, due to age-related decline, physical restrictions, and limited oral health literacy, older Thai adults are less able to control dental plaques and are more likely to have inadequate oral hygiene, poor oral health, and eventually fewer remaining teeth in older ages ( Piyakhunakorn & Sermsuti-Anuwat, 2021a ; Piyakhunakorn & Sermsuti-Anuwat, 2021b ; Sermsuti-Anuwat & Piyakhunakorn, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated that, due to age-related decline, physical restrictions, and limited oral health literacy, older Thai adults are less able to control dental plaques and are more likely to have inadequate oral hygiene, poor oral health, and eventually fewer remaining teeth in older ages ( Piyakhunakorn & Sermsuti-Anuwat, 2021a ; Piyakhunakorn & Sermsuti-Anuwat, 2021b ; Sermsuti-Anuwat & Piyakhunakorn, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it may be not an important issue due to this study being persuasive to estimate the mediation effect of OHL on self‐reported tooth loss. Also, there was a positive association between both education and income (one of the SES components) with OHL on tooth loss, according to a recent study 35 . Third, most variables were dichotomized for data analysis, which leads to a loss of rich information and details, and possibly an underestimation of the variation of outcome between groups 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, there was a positive association between both education and income (one of the SES components) with OHL on tooth loss, according to a recent TA B L E 1 Sample characteristics and association with oral health status (number of missing teeth ≥12) (weighted) among Australian adults in 2013-2014 study. 35 Third, most variables were dichotomized for data analysis, which leads to a loss of rich information and details, and possibly an underestimation of the variation of outcome between groups. 36 However, this approach is simple for statistical analysis and easy interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…2 Older Thais are at a higher risk of age-related health problems, 3 chronic diseases, and noncommunicable diseases, including poor oral health. [4][5][6][7] According to a report from the 8 th Thai National Health Survey in 2017, older Thai adults aged 60-70 years had an average of 18.6 residual teeth, which decreased to 10 among those aged 80-85 years. Older individuals encounter numerous oral hygiene challenges; for example, physical limitations impede plaque control efforts, and chronic diseases may result in a decline in overall well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Older individuals encounter numerous oral hygiene challenges; for example, physical limitations impede plaque control efforts, and chronic diseases may result in a decline in overall well-being. [5][6][7] Healthcare providers should encourage the development of strategies to maximize oral health and prevent complications. Such strategies, particularly those associated with oral health-related behaviors, may improve oral health among older adults.…”
Section: Introductionmentioning
confidence: 99%